Ściganie sprawców kłamstwa katyńskiego w III Rzeszy - Graczyk, Konrad (Z Dziejów Prawa [czasopismo zamknięte], 2020)
This article addresses the criminal liability of German citizens for the so-called Katyń Massacre Lie during the Third Reich. Its source materials are the records of three cases discovered in German archives. Questioning the official (and actual) German propaganda’s ver- sion about the massacre of Polish prisoners of war by the Soviets or negating its perpetration by the Soviets while attributing it to the Germans was subject to prosecution as criminal speech against the state. This paper brings to attention the circumstances under which such an act was committed, the statements said by the perpetrators, and a legal qualification which was grounds for indictment and conviction.